Abandoning historical conflict? : Former political prisoners and reconciliation in Northern Ireland - Shirlow, Peter (Book collections on Project MUSE., 2010)
Drawing on over 150 interviews with former IRA, INLA, UVF and UFF prisoners, this text analyses why Northern Ireland has seen a transition from war to peace.